2008
DOI: 10.1007/s00251-007-0264-0
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 regulates Mx expression in rare minnow Gobiocypris rarus after viral infection

Abstract: Toll-like receptor 3 (TLR3) plays a key role in activating immune responses during viral infection. To study the genes involved in the regulatory function of TLR3 in the rare minnow Gobiocypris rarus after viral infection, a full-length cDNA of TLR3 (GrTLR3) with a splice variant (GrTLR3s) was identified by homologous cloning and RACE techniques. The antiviral effector molecule Mx gene was cloned and partially sequenced. The mRNA expression levels of GrTLR3, GrTLR3s, and Mx were studied in different tissues be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 46 publications
1
30
1
Order By: Relevance
“…TLR3 gene expressions in zebrafish, rainbow trout and rare minnow were also modulated during viral infection [14,16,23]. The kinetics of up-regulation in zebrafish, rainbow trout and rare minnow differed from the present study and may be due to differences in viral kinetics or host factors.…”
Section: Citlr3 Mrna Expression Profile Stimulated By Viral Infectioncontrasting
confidence: 74%
“…TLR3 gene expressions in zebrafish, rainbow trout and rare minnow were also modulated during viral infection [14,16,23]. The kinetics of up-regulation in zebrafish, rainbow trout and rare minnow differed from the present study and may be due to differences in viral kinetics or host factors.…”
Section: Citlr3 Mrna Expression Profile Stimulated By Viral Infectioncontrasting
confidence: 74%
“…Although these diverged more than 500,000 years ago [40] both are commonly used in aquaculture and laboratory research. tlr3 gene expression has been detected in a wide range of tissues of different cyprinid species, with high levels of expression being recorded in skin, liver, gut, gills and spleen [16], [35], [36], [38] and [41]. Studies on the tlr3 genes reported here have confirmed this differential gene expression in organs, for example carp tlr3.1 is highly expressed in mid gut, head kidney and mid kidney, spleen and thymus whilst carp tlr3.2 is predominantly expressed in mid gut, liver and PBLs.…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 is one of the most studied TLRs and several homologues have been found and characterized in different fish species, i.e. zebrafish [34] and [35], rare minnow (Gobiocypris rarus) [36], grass carp [37], common carp [16], rohu (Labeo rohita) [38] and catfish [21]. TLR3 seems to play an important role in the antiviral defense in all vertebrates studies including fish where it has been reported that polymorphisms/haplotypes of Tlr3 in grass carp have significant association with resistance/susceptibility to GCRV [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intestine and liver tissues are susceptible to GCRV (Su et al, 2008), while the spleen is an important immune-organ in this fish species (Fänge and Nilsson, 1985;Press and Evensen, 1999). Therefore, in this present study, RNA-seq sequencing was performed on these four tissues in grass carp before GCRV infection and at six time points post-challenge.…”
Section: Introductionmentioning
confidence: 99%